Kenya : 2006 Article IV Consultation and Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Extension and Rephasing of the Arrangement, Reduction in Access, and Waiver of Performance Criteria; Staff Report; Staff Supplement and Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kenya. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Three years of broad-based economic recovery in Kenya brought GDP growth to nearly 6 percent in 2005/06, its highest in two decades. This 2006 Article IV Consultation focuses on how to sustain Kenya's recent strong economic growth. It argues that this would require accelerating structural reforms and upgrading infrastructure, while preserving macroeconomic stability. The report recommends completion of the Second Review under the Poverty Reduction and Growth Facility (PRGF) arrangement, extension of the arrangement to November 20, 2007, and a reduction and rephasing of access.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet